A miniaturized and integrated dual-channel fluorescence module for multiplex real-time PCR in the portable nucleic acid detection system - Fang, Yile; Wang, Yue; Su, Xiangyi; Liu, Haoran; Chen, Hui; Chen, Zhu; Jin, Lian; He, Nongyue (Frontiers in Bioengineering and Biotechnology, 2022)
A portable nucleic acid detection (PNAD) system based on real-time polymerase chain reaction (real-time PCR) have been developed for point-of-care testing (POCT) of infectious disease pathogens. In order to achieve “sample-in, result-out” while keeping the system compact, the hardware system integrates optical, thermal and motion control modules in a limited space for nucleic acid extraction, purification, amplification and detection. Among these hardware modules, the fluorescence module is one of the most important modules, because its performance directly affects the accuracy and sensitivity of the testing results. In this paper, a miniaturized, high-sensitivity and integrated dual-channel fluorescence module have been proposed for the homemade PNAD system. Based on the principle of confocal optical path, two group of excitation-emission optical paths of different wavelengths are integrated in a small space. In terms of circuitry, a current-light dual negative feedback light-emitting diode (LED) drive circuit is applied to improve the stability of the excited light source. All optical and electronic components are integrated in a metal box of 55 mm × 45 mm × 15 mm, that helps miniaturize the detection system. Two different modules have been assembled to fit various fluorescent dyes or probes with the set of excitation and emission as follow: module 1#: 470 nm/525 nm, 570 nm/630 nm; module 2#: 520 nm/570 nm, 630 nm/690 nm. Finally, hepatitis B virus (HBV) concentration gradient detection and multiplex detection of different gene targets of SARS-CoV-2 are carried out on the PNAD system equipped with these two fluorescence modules for evaluating their performances. Compared with the commercial real-time PCR instrument, our fluorescence module has good stability and detection sensitivity.